Haunted house murder - Meier, Leslie; Hoss, Eliza; Hollis, Lee; Ross, Barbara, 1953-; Recorded Books, Inc. (Prince Frederick, Md. : Recorded Books, 2019)
DEATH BY HAUNTED HOUSE by LEE HOLLIS: For the past two years, the house next door to Hayley Powell has sat abandoned after the owner died under mysterious circumstances. The Salinger family has recently taken possession of the property, but the realtor behind the deal has vanished--after a very public and angry argument with Damien Salinger. If Bar Harbor's newest neighbors are murderers, Hayley will haunt them until they confess.
HALLOWED OUT by BARBARA ROSS: With its history of hauntings and ghost sightings, Busman's Harbor is the perfect setting for Halloween festivities. But when a reenactment of a Prohibition-era gangster's murder ends with a literal bang and a dead actor from New Jersey, Julia Snowden must identify a killer before she ends up sleeping with the fishes.
HAUNTED HOUSE MURDER by LESLIE MEIER: Newcomers to Tinker's Cove, Ty and Heather Moon have moved into a dilapidated house reputed to be a haven for ghosts. Now strange noises and flickering lights erupt from the house at all hours and neighborly relations are on edge. And when a local boy goes missing near the house, it's up to Lucy Stone to unravel the mystery of the eccentric couple and their increasingly frightful behavior.
Compact disc.
In container (17 cm).
Title from container.
Narrated by Eliza Foss.
Keywords: Haunted houses -- Fiction; Murder -- Fiction; Missing persons -- Fiction; Women private investigators -- Fiction; Halloween -- Fiction; Audiobooks; Mystery fiction